The Mythic Experience: The Audiovisual Spectacle of the Biwa Hoshi Narrative and Performance in Ghost of Tsushima - Carmel Anne B. Abela ([sic])
The Mythic Tales side quests in Ghost of Tsushima (2020) explore folkloric and supernatural narratives using the themes from legends and lore surrounding Tsushima Island. However, as a historical video game that reimagines a thirteenth-century medieval Japanese society during the events of the Mongol invasion of Japan in 1274, careful examination of its represented form is necessary since it can tell us how a player is instructed to play with the reimagined past or what about the past is deemed important (Chapman; Balela and Mundy; McCall). Furthermore, the side quests provide a deeper exploration of the game-world setting, which can provide a historical and sociocultural understanding of the represented past through gameplay. In line with this, this paper examines the Mythic Tales experience by exploring the representations of the in-game version of a Japanese traditional performance art called the heikyoku, performed by a medieval storyteller known as the biwa hoshi. This includes a discussion of the tradition and how it translates into a video game format, highlighting the special audiovisual spectacle that relies on familiar Japanese imageries such as the sumi-e and ukiyo-e, which are unique to this part of the game. A case study of one of the Mythic Tales, “The Curse of Uchitsune,” will serve as critical analysis toward the kind of in-game mythic narrative and experience the game provides.